Students’ Mathematical Literacy Problem-Solving Skills Based on Krulik and Rudnick’s Theory - Dina Anugrahani; Indriati Nurul Hidayah (Universitas Wiralodra, 2026)
This study sought to describe high school students’ mathematical literacy problem-solving skills based on the stages of Krulik and Rudnick. A qualitative descriptive approach was adopted. Data were obtained from a mathematical literacy task and semi-structured interviews. The participants comprised tenth-grade students from a senior high school in Malang Regency, who were classified into high, medium, and low categories. One subject from each category was purposively selected for an in-depth investigation. The data were analyzed following the interactive model proposed by Miles, Huberman, and Saldana, consisting of data condensation, data display, and conclusion drawing. The findings revealed that the subject in the high category fulfilled all indicators across every stage of Krulik and Rudnick’s framework. The subject in the medium category fulfilled most indicators but demonstrated limitations at the Select a Strategy stage by failing to identify all possible solutions and at the Reflect and Extend stage by not fulfilling all indicators. In contrast, the subject in the low category fulfilled only the indicators at the Read and Think stage and several indicators at the Explore and Plan stage, while failing to fulfill the indicators at the subsequent stages.